Manual guidance in gymnastics: a case study - Heinen, T.; Vinken, P.; Ölsberg, P. (Science of Gymnastics Journal, 2010)
Although the use of manual guidance in gymnastics is widely spread, little is known about the effects of this technique on movement kinematics. The goal of this case study was to evaluate the effects of two manual guidance procedures on movement kinematics of a back handspring and a back tuck somersault following a round-off on the floor. Based on assumptions of high-level coaches it was predicted that the sandwich-grip would have different effects on movement kinematics in both skills than the iliac crest/thigh-grip. We analyzed performance of n = 6 female gymnasts in the two skills with and without guidance. Manual guidance had significant effects on different kinematic parameters in both skills. From our results we concluded, that the sandwich-grip should be applied in the first instance if the coach`s interest is to optimize the angular momentum about the somersault axis and the second flight phase in the back handspring. The optimal guidance procedure in the round-off back tuck somersault routine would be a mixture of both, the sandwich-grip and the iliac crest/thigh-grip.